Decompressive Hemicraniectomy Associated With Ultrasound-Guided Minimally Invasive Puncture and Drainage Has Better Feasibility Than the Traditional Hematoma Evacuation for Deteriorating Spontaneous Intracranial Hemorrhage in the Basal Ganglia Region: A Retrospective Observational Cohort Study - Cheng, Yuan; Chen, Jin; Zhao, Guanjian; Xie, Zongyi; Huang, Ning; Yang, Qiang; Chen, Weifu; Huang, Qin (Frontiers in Neurology, 2021)
Objectives: Spontaneous intracerebral hemorrhage (ICH) is a devastating disease with higher mortality and disability rates; however, ideal surgical management is still to be determined for critical ICH. The purpose of this study was to prove the feasibility and unique clinical value of a novel combination, decompressive hemicraniectomy associated with ultrasound-guided minimally invasive puncture and drainage (DH + MIPD), for deteriorating ICH in the basal ganglia region. Methods: According to the enrollment criteria, 168 ICH patients were analyzed retrospectively, of which 86 patients received DH + MIPD and 82 patients received DH associated with traditional hematoma evacuation as the control group. The change process of three parameters, including hematoma size, peri-hematoma edema, and intracranial pressure (ICP), in a period of time after operation, as well as the short- and long-term therapeutic effect, was compared. Results: The DH + MIPD method could effectively achieve the evacuation rate of hematoma up to 87% at 5 days post-operation and had the significant advantages of minimal injury to cerebral tissue, less degree of edema, better effect of decreasing ICP, shorter operation time, less blood loss, and lower mortality compared with the control method. The DH + MIPD group had a significantly higher survival rate within 1 year post-operation (P = 0.007) and better functional outcome at 90 and 180 days post-operation (P = 0.004). A subgroup analysis pointed out that the DH + MIPD method had a definite survival advantage for critical ICH patients older than 60 years old and with hematoma located in the left dominant hemisphere. Conclusions: Our results proved the better feasibility of DH + MIPD on hematoma evacuation and implicated its significant advantages of reducing mortality and improving functional recovery. This method provides one more choice for the individualized therapy of ICH in the basal ganglia region.